2019
DOI: 10.1038/s41467-019-10092-5
|View full text |Cite
|
Sign up to set email alerts
|

Three phylogenetic groups have driven the recent population expansion of Cryptococcus neoformans

Abstract: Cryptococcus neoformans ( C. neoformans var. grubii ) is an environmentally acquired pathogen causing 181,000 HIV-associated deaths each year. We sequenced 699 isolates, primarily C. neoformans from HIV-infected patients, from 5 countries in Asia and Africa. The phylogeny of C. neoformans reveals a recent exponential population expansion, consistent with the increase in the number of susceptible hosts. In our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
73
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 47 publications
6
73
0
1
Order By: Relevance
“…These data suggest that VNIa-5 isolates have increased pathogenic potential. Of note, we do not observe clustering of isolates within the VNIa-5 lineage according to host immune status, signifying that the entire lineage has the potential to cause disease in immunocompetent people 2 .…”
Section: Introductionmentioning
confidence: 55%
See 4 more Smart Citations
“…These data suggest that VNIa-5 isolates have increased pathogenic potential. Of note, we do not observe clustering of isolates within the VNIa-5 lineage according to host immune status, signifying that the entire lineage has the potential to cause disease in immunocompetent people 2 .…”
Section: Introductionmentioning
confidence: 55%
“…We have previously shown that the VNIa-5 lineage is strongly associated with disease in apparently immunocompetent patients 2,3 . Both VNIa-5 and VNIa-4 frequently affect our (severely immunosuppressed) HIV-infected patients 2,3 . VNIa-4 rarely causes disease in HIV-uninfected patients, and when it does, the patients are significantly more likely to have underlying diseases associated with immunosuppression 9 .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations